PENGENALAN POLA ALPHABET TULISAN TANGAN SECARA ON-LINE DENGAN JST-BP - Tole Sutikno; Andhy Fathurrakhman (Universitas Ahmad Dahlan, 2005)
The intelligent system based in the backpropagation artificial neural network and image processing with GUI Matlab 7.0 was developed. This system is designed for on-line pattern recognition. In this experiments, system are trained dan tested using capital alfabet handwriting patterns that captured from on-line webcam automatically. Generally, the results of the experiments show that the system could recoginize with a high accuracy.